1972
DOI: 10.1002/qj.49709841506
|View full text |Cite
|
Sign up to set email alerts
|

Nucleation of water drops by Brownian contact with AgI and other aerosols

Abstract: SUMMARYAitken-sized (0.01pm) particles of AgI, CuI, and 'contaminated' Ag,O were able to nucleate various sized water droplets in free fall (20-80@ni in radius) by a direct, diffusive (Brownian) contact mechanism. The AgI aerosol was found to be the most efficient nucleator, showing a probability of 100 per cent at -16"C, 50 per cent at about -14"c, and 1 per cent at -11°C. These nucleation characteristics for AgI can be modelled from heterogeneous nucleation theory if the value of the contact parameter is ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1973
1973
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The analysis of immersion freezing studies in Fig. 2 suggests that freezing temperatures are higher for those studies where the particle is free to take a position on the surface of the droplet, as is the case for experiments performed with IMCA-ZINC or with a cloud chamber, as in the study by Sax and Goldsmith (1972).…”
Section: Position Of Particles In or On The Dropletmentioning
confidence: 92%
See 3 more Smart Citations
“…The analysis of immersion freezing studies in Fig. 2 suggests that freezing temperatures are higher for those studies where the particle is free to take a position on the surface of the droplet, as is the case for experiments performed with IMCA-ZINC or with a cloud chamber, as in the study by Sax and Goldsmith (1972).…”
Section: Position Of Particles In or On The Dropletmentioning
confidence: 92%
“…Assuming a collision efficiency of ca. 0.3, around 100 particles would be captured by the droplet (note that this number is higher than the collection of only 1 particle estimated by Sax and Goldsmith, 1972). For immersion freezing experiments, the droplets passed the aerosol stream at T > 273 K before they were cooled to the target temperature.…”
Section: Cloud Chamber Experimentsmentioning
confidence: 94%
See 2 more Smart Citations
“…Phys., 13, 9745-9769, 2013 www.atmos-chem-phys.net/13/9745/2013/ drops. Langer et al (1978) determined the freezing probabilities of AgI particles using the mathematical expression from Sax and Goldsmith (1972). They found that the freezing probabilities increased with decreasing temperature from 259 K to 253 K. In addition, an aerosol particle size effect was clearly observed.…”
Section: Mixing Cloud Chambersmentioning
confidence: 99%